2021
DOI: 10.3389/fneur.2021.731237
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease Burden Related to Carotid Intraplaque Hemorrhage Serves as an Imaging Marker for Clinical Symptoms in Carotid Stenosis

Abstract: Objectives: In patients with carotid stenosis, to investigate the relationship between carotid intraplaque hemorrhage (IPH) and total burden of cerebral small vessel disease (CSVD) and preliminarily explore whether the total CSVD burden as an imaging marker can distinguish the severity of clinical symptoms.Methods: A total of 108 patients (the mean age was 66 ± 7 years, and 85.2% were male) with unilateral carotid stenosis ≥50% underwent brain MRI and high-resolution MRI for carotid plaque characterization. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the current study, we used IAP, identified by HRMRI, as an imaging marker of intracranial artery atherosclerosis, which can provide more information of intracranial atherosclerosis compared with these previous methods. Previous studies showed that carotid vulnerable plaque is related to CSVD burden 4 , 6 , 39 , 40 . Given that complicated plaques may represent active artery atherosclerosis, there is reason to believe that such plaques may be more likely associated with the cerebral small vessel.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the current study, we used IAP, identified by HRMRI, as an imaging marker of intracranial artery atherosclerosis, which can provide more information of intracranial atherosclerosis compared with these previous methods. Previous studies showed that carotid vulnerable plaque is related to CSVD burden 4 , 6 , 39 , 40 . Given that complicated plaques may represent active artery atherosclerosis, there is reason to believe that such plaques may be more likely associated with the cerebral small vessel.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, CSVD markers only including WMHs, EPVS, CMBs, and lacunes is incomplete due to inclusion of recent small subcortical infarcts and brain atrophy. Sixth, contrast enhancement was not used in the current cohort, given that contrast enhancement of atherosclerotic plaque is a strong, reliable marker of culprit plaques 40 . Seventh, we only investigated the association in CSVD and ESUS populations due to lack of HR-MRI data in other stroke subtypes.…”
Section: Discussionmentioning
confidence: 99%